2019
DOI: 10.1111/ijn.12772
|View full text |Cite
|
Sign up to set email alerts
|

Application of heat and a home exercise program for pain and function levels in patients with knee osteoarthritis: A randomized controlled trial

Abstract: Aim This study aimed to determine the effect of application of superficial local heat and a home exercise program on pain and function levels to patients with bilateral knee osteoarthritis. Methods This study was conducted in Turkey between January 2014 and February 2015. The sample group of the study consisted of 62 patients with osteoarthritis; 15 assigned to heat application, 15 to exercise, 15 to exercise after heat application, and 17 for the control group. While the patients in the control group received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 29 publications
0
21
0
1
Order By: Relevance
“…Concerning selection bias, most of the studies don't give information about the way the random sequence generation was performed, with only five being considered low risk of bias (DeVita et al, 2018;Dias et al, 2017;Karadağ, Taşci, Doğan, Demir, & Kiliç, 2019;Shellington, Gill, Shigematsu, & Petrella, 2019;Silva et al, 2015). However, most of the studies describe how the allocation concealment was done, being considered low risk of bias.…”
Section: Assessment Of Methodological Quality Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning selection bias, most of the studies don't give information about the way the random sequence generation was performed, with only five being considered low risk of bias (DeVita et al, 2018;Dias et al, 2017;Karadağ, Taşci, Doğan, Demir, & Kiliç, 2019;Shellington, Gill, Shigematsu, & Petrella, 2019;Silva et al, 2015). However, most of the studies describe how the allocation concealment was done, being considered low risk of bias.…”
Section: Assessment Of Methodological Quality Of Studiesmentioning
confidence: 99%
“…However, most of the studies describe how the allocation concealment was done, being considered low risk of bias. Only six studies lack information about it, leaving the possibility of bias unclear (DeVita et al, 2018;Ha, Yoon, Yoo, Kang, & Ko, 2018;Huang et al, 2020;Karadağ et al, 2019;Liu et al, 2019;Mazloum, Rabiei, Rahnama, & Sabzehparvar, 2018).…”
Section: Assessment Of Methodological Quality Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the reason for the decrease, albeit small, in the VAS-Pain score and WOMAC-Pain sub-scale, WOMAC-Stiffness sub-scale, and WOMAC-Physical function sub-scale scores of the individuals in the hot compress group at the end of the 7-day application, is thought to be conditions such as increased circulation by vasodilation due to the effect of the temperature in the area where heat was applied, decreased pressure and tension on nerve endings, reduced pain, and relaxed muscles as a result of removing metabolic residues that cause pain from the region. No studies conducted on the waist region as an application area for reducing pain in knee OA were encountered in the literature, only studies on the application on the knee region have been identified 33,[44][45][46][47][48] .…”
Section: Discussionmentioning
confidence: 99%
“…üzerine etki ederek kas, tendon, kapsül ve ligamanlarda esneklik artışına neden olur. Sıcaklığı etkisiyle ayrıca hücresel metabolizmada hızlanma ve analjezik etki sağlar 24. Fakat bu yöntemde cildi ısıtma süresi ve sıcaklık derecesi etkin bir şekilde kontrol edilemediğinden ciltte yanıklar meydana gelebilmektedir 15,22.…”
unclassified